If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + -2) = -10(-2x + 1) Reorder the terms: 5(-2 + 4x) = -10(-2x + 1) (-2 * 5 + 4x * 5) = -10(-2x + 1) (-10 + 20x) = -10(-2x + 1) Reorder the terms: -10 + 20x = -10(1 + -2x) -10 + 20x = (1 * -10 + -2x * -10) -10 + 20x = (-10 + 20x) Add '10' to each side of the equation. -10 + 10 + 20x = -10 + 10 + 20x Combine like terms: -10 + 10 = 0 0 + 20x = -10 + 10 + 20x 20x = -10 + 10 + 20x Combine like terms: -10 + 10 = 0 20x = 0 + 20x 20x = 20x Add '-20x' to each side of the equation. 20x + -20x = 20x + -20x Combine like terms: 20x + -20x = 0 0 = 20x + -20x Combine like terms: 20x + -20x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| y=4(-2)-6 | | 183-4x=32x+23 | | (x+7)(4x*-5)=0 | | .3x^2=1.8x+.3 | | 39x+35=620 | | x=2(2)+8 | | x=2(1)+8 | | 3s=-21 | | 9x-5=283 | | x=2(0)+8 | | x=2(-1)+8 | | x=2(-2)+8 | | x-17=37 | | -6+5(6+x)=5x+45 | | 6y+y=42 | | 0.3x^2=1.8x+.03 | | -2x^2=4x-3 | | -12(7-4x)=-4(1-2x) | | x+x+1.04=79.06 | | 5a=8a-5 | | 10yx^2+35y^2x= | | x=-5(2)+6 | | 6(-5x-7)=-222 | | x=-5(1)+6 | | -9+8k= | | x=-5(0)+6 | | -15+8m=5+7(2+6m) | | x=-5(-1)+6 | | 30y+42= | | 2x+7=-x^2 | | x=-5(-2)+6 | | 2x^2-7x-1=0 |